Developing an empirical model for assessment of total nitrogen inflow to rivers and lakes in the Biebrza river watershed, Poland - Jessica Canchig; Rinda Kustina; Mateusz Grygoruk (Przegląd Naukowy Inżynieria i Kształtowanie Środowiska, 2023)
Nitrogen load is crucial for its application in various fields such as agriculture and improving water quality control for authorities responsible for establishing agricultural policies in the area. The calculation of nitrogen load using existing equations is not applicable for all types of rivers, thus requiring the development of a new equation that can be applied to lakes and rivers in the Biebrza river catchment. To determine the new equation, extensive mapping of the catchment area was conducted, which was adjusted to precipitation and runoff in the area, allowing the observed results to be compared. Based on several analyses, the new equation has better accuracy, RMSE of the new model-based estimation decreased by 65.9% in 2005–2015 and 62.2% in 2016–2021 for river and 92% in 2008–2019 and 95% in 2020–2021 for lakes. Therefore, the application of the new calibrated empirical model provides results close to the real values and it can be used in the Biebrza river basin to simulate the total nitrogen runoff.